Investigation of Erosion-Induced Groundwater Pollution in Selected Wells Around Kwarin Awaja, Birnin Kudu, Nigeria - Amoo, Afeez Oladeji; Adeleye, Adeniyi Olarewaju; Ijanu, Emmanuel Madu; Mallam, Ibrahim; Asaju, Catherine Iyabode; Amoo, Florence Kemi; Adeleye, Olukemi; Amoo, Nureni Babatunde; Salisu, Shehu Abdullahi (CV. Literasi Indonesia, 2025)
Soil erosion in semi-arid regions contributes significantly to groundwater contamination, particularly through sediment-laden runoff entering shallow aquifers. The intensification of rainfall events has accelerated surface erosion, leading to increased transport of sediments and contaminants into shallow wells, which serve as the primary water source for many households. This study investigated the extent and mechanisms of groundwater contamination in twelve selected wells around Kwarin Awaja, focusing on changes in water quality before and after major rainfall events. Water samples were analyzed for turbidity, electrical conductivity (EC), pH, coliform bacteria, nitrates, and heavy metals (cadmium and chromium). Results showed significant increases in turbidity, nitrates, total dissolved solids, chloride, sulphate, and electrical conductivity after rainfall, indicating erosion-induced pollutant infiltration. Paired sample t-tests revealed significant post-rainfall increases in turbidity (up to 12.1 NTU) and EC (up to 675 µS/cm), with values exceeding national standards such as Nigeria Standards for Drinking Water Quality (NSDWQ) in wells closest to active erosion sites. Pearson correlation analysis showed strong associations between proximity to erosion features and elevated pollution indicators. Microbial contamination, absent before rainfall, was detected in several wells after rainfall events. The findings highlight the vulnerability of shallow groundwater to erosion-driven pollution and underscore the need for targeted interventions to protect water quality in erosion-prone rural environments.